Ecological Strategy of Development in Agricultural Enterprises of Ukraine - PIZNIAK, Tetiana; KOVALOVA, Olha; NOVIKOVA, Olha (Journal of Environmental Management and Tourism, 2020)
The paper discusses the importance of green agricultural production in Ukraine and expected benefits of such strategy. Main directions of implementing ecological development strategy of agricultural enterprises in Ukraine are outlined. A system of economical incentives for implementation of ecological development strategy of agricultural enterprises is introduced and analysed. We also considervariousdeterrents with extra liabilities to be used for the companies which violate ecological principles and regulations. A system of investment filters based on ecological economy performance of the agricultural enterprises is developed. The significance of all these factors for the enterprises is determined through the use of factorial analysis and questionnaires and surveys. More than 100 companies took part in the research and ranked possible benefits for the enterprises after implementing ecological strategy and possible stimulation.